Analisis Pengaruh ROCE dan ROE Terhadap Dividend Yield: (Studi pada Perusahaan Sub Sektor Farmasi Yang Terdaftar di BEI) - Faahtiah, Suraya; Rahmatia, Nafisah Nurul; Huda, Nurul (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to find out and explain the influence of ROCE and ROE on Dividend Yield. The method used is quantitative, with secondary data sources from pharmaceutical companies listed on the IDX. The results of the study stated that there was no partially significant effect of ROCE on Dividend Yield, there was no partial significant effect of ROE on Dividend Yield in Pharmaceutical Sub-Sector Companies Listed on the IDX, and there was no simultaneous significant effect of ROCE and ROE on Dividend Yield in Pharmaceutical Sub-Sector Companies Listed on the IDX, with an influence of 51.6% while 48.4% was influenced by other variables.